(untitled) - Bhandari, Humnath (Japan, 2009)
Contents: Introduction, human values - an overview, human values and economic, development, research design, human values in Asian societies - an empirical investigation,...
Keywords: Sustainable development,Phát triển bền vững; Asia,Châu Á